SAT0097 Predicting Cardiovascular Risk in Patients with Rheumatoid Arthritis. (9th June 2015) - Agca, R.; van Sijl, A.M.; Voskuyl, A.E.; Nurmohamed, M.T.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease with an enhanced cardiovascular (CV) risk. Classical risk factors for cardiovascular disease (CVD) do not fully explain this elevated risk. Existing risk prediction models generally either underestimate or overestimate this CV risk in RA patients. Accurate tools for predicting the development of CVD in an RA population still lack. Objectives: To investigate the predictive value of several clinical and soluble markers of CVD in a prospective observational cohort of longstanding RA patients. Methods: Baseline sera and blood were collected and stored for 353 RA patients participating in an ongoing prospective cohort study to assess cardiovascular morbidity and mortality (CARRΈ study). Cardiovascular end points were defined as a verified medical history of coronary, cerebral or peripheral arterial disease. A backward selection model was used to identify predictor variables for incident CVD. Variables with a p-value above 0.1 were excluded. Results: During 10 years of follow up 58 patients had developed CVD. The majority of the patients were female (65.7%) with a mean age of 63±6 years and a mean RA duration of 8±4 years. Male gender (OR 2.30, 95%CI 1.19 – 4.42; P=0.013), older age (OR 1.05, 95%CI 1.00 – 1.09; P=0.047) a higher systolic blood pressure (OR 1.02, 95%CI 1.01 – 1.04; P=0.005), an elevated serum creatinin level (OR 1.02, 95%CI 1.00 – 1.03; P=0.094) and a serum high density lipoprotein (HDL) below 1.0 mmol/l (OR 2.00, 95% CI 0.97 – 4.12; P=0.059) predicted CVD development in a multivariable model with an area under the receiver operating characteristics curve (AUC) of 0.75 (95%CI 0.69 – 0.81), indicating a moderate to good discriminatory capacity for CVD development within this population. RA duration, disease activity score (DAS28), rheumatoid factor (RF), anti-cyclic citrulline peptide antibody (anti-CCP), diabetes, smoking, body mass index (BMI), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), total cholesterol (TC), low density lipoprotein (LDL), triglycerides, apolipoprotein A-I (Apo A-I), apolipoprotein B (Apo-B) and serum uric acid didn't predict CVD development (data not shown). Conclusions: CV risk can be predicted by gender, age, systolic blood pressure, serum creatinine and serum HDL in patients with longstanding RA. Additional studies are needed to investigate whether adding other biomarkers related to CVD will improve the predictive capacity of this model. Disclosure of Interest: None declared